Accounting and raison d'État in the Grand Duchy of Tuscany: Reopening the University of Pisa (1543–1609). (October 2018) - Bigoni, Michele; Funnell, Warwick; Verona, Roberto; Deidda Gagliardo, Enrico
Abstract: The University of Pisa in the 16th and early 17th centuries was essential to the governmental plan of the Grand Dukes of Tuscany to strengthen their State. Consistent with the rationality of Foucault's concept of raison d'État, the Grand Dukes sought to constantly mould the conduct of students and professors through a multitude of interventions. These often contradicted the law in the form of the Statute under which the University was reopened that promised to protect the freedom and independence of students and professors. Detailed control by the Grand Dukes was enabled by an extensive use of written information, most notably in the form of accounting reports, which made it possible for the rulers to govern the University in a detailed and thorough way.